IS26-Mediated Precise Excision of the IS26-aphA1a Translocatable Unit - Christopher J. Harmer (American Society for Microbiology, 2015)
ABSTRACT We recently showed that, in the absence of RecA-dependent homologous recombination, the Tnp26 transposase catalyzes cointegrate formation via a conservative reaction between two preexisting IS26, and this is strongly preferred over replicative transposition to a new site. Here, the reverse reaction was investigated by assaying for precise excision of the central region together with a single IS26 from a compound transposon bounded by IS26. In a recA mutant strain, Tn4352, a kanamycin resistance transposon carrying the aphA1a gene, was stable. However, loss of kanamycin resistance due to precise excision of the translocatable unit (TU) from the closely related Tn4352B, leaving behind the second IS26, occurred at high frequency. Excision occurred when Tn4352B was in either a high- or low-copy-number plasmid. The excised circular segment, known as a TU, was detected by PCR. Excision required the IS26 transposase Tnp26. However, the Tnp26 of only one IS26 in Tn4352B was required, specifically the IS26 downstream of the aphA1a gene, and the excised TU included the active IS26. The frequency of Tn4352B TU loss was influenced by the context of the transposon, but the critical determinant of high-frequency excision was the presence of three G residues in Tn4352B replacing a single G in Tn4352. These G residues are located immediately adjacent to the two G residues at the left end of the IS26 that is upstream of the aphA1a gene. Transcription of tnp26 was not affected by the additional G residues, which appear to enhance Tnp26 cleavage at this end. IMPORTANCE Resistance to antibiotics limits treatment options. In Gram-negative bacteria, IS26 plays a major role in the acquisition and dissemination of antibiotic resistance. IS257 (IS431) and IS1216, which belong to the same insertion sequence (IS) family, mobilize resistance genes in staphylococci and enterococci, respectively. Many different resistance genes are found in compound transposons bounded by IS26, and multiply and extensively antibiotic-resistant Gram-negative bacteria often include regions containing several antibiotic resistance genes and multiple copies of IS26. We recently showed that in addition to replicative transposition, IS26 can use a conservative movement mechanism in which an incoming IS26 targets a preexisting one, and this reaction can create these regions. This mechanism differs from that of all the ISs examined in detail thus far. Here, we have continued to extend understanding of the reactions carried out by IS26 by examining whether the reverse precise excision reaction is also catalyzed by the IS26 transposase.